2017
DOI: 10.1007/978-3-319-55231-6_31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motor Imagery on Cognitive Function and Prefrontal Cortex Activity in Normal Adults Evaluated by NIRS

Abstract: Recent near-infrared spectroscopy (NIRS) studies demonstrated that physical exercise enhances working memory (WM) performance and prefrontal cortex (PFC) activity during WM tasks in normal adults. Interestingly, the effects of rehabilitation (i.e. physiotherapy) on post-stroke patients could be enhanced by motor imagery (MI), an active process during which the specified action is reproduced within WM without any actual physical movement. However, it is not known whether MI can enhance cognitive function and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…We suggest that these processes are identifiable with the dorsolateral prefrontal cortex (DLPFC). Concordant with this view, studies show greater activity in DLPFC during motor imagery than overt actions (Guillot et al 2009), that this tendency increases for less familiar actions (Zhang et al 2018), and that motor imagery training can increase the responsiveness of DLPFC (Moriva and Sakatani 2017). The suggested role of executive functions in motor imagery is also consistent with the putative critical role of the DLPFC in executive functions (Niendam et al 2012;Yuan and Raz 2014).…”
Section: Discussionmentioning
confidence: 68%
“…We suggest that these processes are identifiable with the dorsolateral prefrontal cortex (DLPFC). Concordant with this view, studies show greater activity in DLPFC during motor imagery than overt actions (Guillot et al 2009), that this tendency increases for less familiar actions (Zhang et al 2018), and that motor imagery training can increase the responsiveness of DLPFC (Moriva and Sakatani 2017). The suggested role of executive functions in motor imagery is also consistent with the putative critical role of the DLPFC in executive functions (Niendam et al 2012;Yuan and Raz 2014).…”
Section: Discussionmentioning
confidence: 68%
“…A recent nearinfrared spectroscopy study in healthy adults suggested that MIT improves the behavioural performance of working memory and enhances prefrontal cortex activity induced by the working memory task. 38 In addition, recent studies have also suggested that MIT can improve cognitive functions in people with stroke and Parkinson's disease. 39,40 Our study has provided novel evidence on the efficacy of a Tele-MIT programme on cognitive functions in pwMS.…”
Section: Discussionmentioning
confidence: 99%
“…TMS may have slightly disrupted performance in the spatial span task but did not appear to affect performance in the Go/NoGo or switching tasks. This could suggest many possibilities: Most parsimoniously, it may be that working memory is the executive function most important to motor imagery, as suggested by a study showing improvement in working memory after motor imagery training [40], and that inhibition and/or task switching are less important, or not important at all. More speculatively, it may be that motor imagery shares with all these tasks a common pool of executive resources, and that the cognitive tasks did not use enough of these executive resources to be clearly affected by TMS.…”
Section: Methodsmentioning
confidence: 99%
“…For one, numerous studies have observed a greater activation in the DLPFC during motor imagery than overt action [18,[29][30][31][32][33][34][35][36][37][38], with this activation being even greater for novel movements [34,39]. For another, motor imagery training has been shown to improve working memory through an increase in prefrontal cortical activity [40], and coupling from Supplementary Motor Area to DLPFC is critical during motor imagery [41,42], with higher connectivity at restingstate predicting greater performance [43,44].…”
Section: Introductionmentioning
confidence: 99%